2017
DOI: 10.1016/j.chb.2017.07.020
|View full text |Cite
|
Sign up to set email alerts
|

The impact of daily emotional demands, job resources and emotional effort on intensive internet use during and after work

Abstract: Information Communication Technologies (ICTs) have become a popular leisure platform. Psychological recovery during leisure time is vital to replenish resources spent at work. The present diary study comprised a sample of employees with high exposure to emotional demands and integrates the Job Demands-Resources (JD-R) and addiction literature to examine whether engaging intensively on the internet may be conductive or inhibitor to psychological recovery. A total of 84 employees completed four consecutive daily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 66 publications
1
19
0
Order By: Relevance
“…Given that many of us spend hours a day online for work purposes (myself included) clearly demonstrates that how the medium of the Internet is used is much more important than the time spent in the medium when defining IA. Even when the excessive use of the Internet is work-based and causing long-term negatively detrimental effects on the individual, such individuals would be defined and conceptualized as work addicts rather than Internet addicts (Quinones and Griffiths 2017 ; Quinones et al 2016 ).…”
Section: Internet Addiction Vs Internet-based Addictions: Some Furthmentioning
confidence: 99%
“…Given that many of us spend hours a day online for work purposes (myself included) clearly demonstrates that how the medium of the Internet is used is much more important than the time spent in the medium when defining IA. Even when the excessive use of the Internet is work-based and causing long-term negatively detrimental effects on the individual, such individuals would be defined and conceptualized as work addicts rather than Internet addicts (Quinones and Griffiths 2017 ; Quinones et al 2016 ).…”
Section: Internet Addiction Vs Internet-based Addictions: Some Furthmentioning
confidence: 99%
“…On the positive side, social media creates unprecedented opportunities for those in need of social support in real life to be satisfied online (Notredame et al, 2018). Quinones and Griffiths (2017) found that releasing emotional expression and capturing social resources were the primary driving forces for intensive social media use. The socio-psychological needs for social support would lead individuals to more frequent social media use for expanding their social networks online, through maintaining old interpersonal relationships and building new ones, with the hope that their friends or followers on social media may provide social and psychological support when they are in need (Indian & Grieve, 2014;Wohn & Larose, 2014).…”
Section: Social Media Use Family Environment and Self-esteemmentioning
confidence: 99%
“…Although a positive impact of technology use such as smartphones and the Internet on recovery experiences at work or after work has been found in recent studies (Quinones & Griffiths, 2017;Rhee & Kim, 2016), the relationship between social media break activities and at-work recovery experiences is still not clear. More specifically, based on the measurement of four types of break activities (Kim et al, 2017(Kim et al, , 2018, there is only one item in social activity related to social media use, which is checking personal social networking sites such as Facebook and Twitter.…”
Section: Research Backgroundmentioning
confidence: 98%
“…This industry's specific characteristics create unique job demands for hospitality workers such as "face time" between employees and customers. Such interactions require employees to follow a company's expectations and norms of appropriate emotional expression, such as keeping calm and reacting with understanding to customers and suppressing their own emotions when dealing with service failures from upset and angry customers (Quinones & Griffiths, 2017). To interact with customers in an effective way, employees need to alter how they feel and what feelings they show (Grandey, 2000).…”
Section: Research Backgroundmentioning
confidence: 99%
See 1 more Smart Citation